Liposomes as vaccine carrier in hatchery vaccination against infectious bursal disease in broiler chickens - Wahab, Mukminah Sakinah; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Liposome is one of the nano-based carriers with structural similarity to cell membrane. Application of liposomes in infectious bursal disease (IBD) vaccine may enhance vaccine delivery process. It was the objective of this study to determine the effectiveness of cationic liposomes in induction of IBD antibody in broiler chickens. Eighty five day old broiler chicks were divided into 4 groups namely the IBD, Covac, Sevac and Control. The chicks in the IBD group were vaccinated with commercial IBD vaccine (My Hatch UPM93) with virus titre of 103 EID50 / 0.1mL. The chicks in the Covac group were vaccinated with combination 1:2 ratio of cationic liposomes and My Hatch UPM93, whereas the chicks in the Sevac group were vaccinated with combination 1:2 ratio of cationic liposomes and working IBDV seed virus (MyHatch UPM93). The chicks in all groups were vaccinated at day old at hatchery (hatchery vaccination) via subcutaneous inoculation. The chicks in the Control group were not vaccinated. All chicks in the groups were sacrificed at various intervals and prior to necropsy, the body weights of chicks were recorded, and blood samples were collected. On necropsy, the bursa weight were recorded and fixed into 10% formalin. The study showed that the chickens from all groups did not exhibit any abnormal clinical signs and gross lesions throughout the trial, except reduced in bursal weight and bursal to body weight ratio were recorded at day 28 pv in IBD, Covac and Sevac groups when compared to the Control. The lesion scoring of the bursa of Fabricius in the Control group remained low throughout the trial. The lesion scoring in the Covac group was slightly increased at days 21 and 28pv. A similar pattern was recorded in the Sevac group. However, the lesion scoring in the IBD group was only recorded to increase at day 28. It is interesting to note that the bursa lesion scoring is directly related to the level of IBD antibody: the severe the lesion the high antibody titre was induced. The IBD antibody titre in the Control group was continued to decrease (p<0.05) from days 0 to 28. The antibody titre in the IBD group was started to increase significantly (p<0.05) at day 28pv. The antibody titre in the Covac and Sevac groups were started to increase at days 21 and 28 pv. Despite low amount of IBDV dosage used in Covac (2/3) when compared to IBD group, the results showed that the chickens in the Covac group showed higher lesion scoring and IBD antibody titre when compared to the IBD group. It was concluded that the application of cationic liposomes can enhance the delivery of IBDV vaccine to the target organ, the bursa of Fabricius and induce high and protective level of IBD antibody titre with mild bursal lesion. Hatchery vaccination using UPM93 IBDV strain either with or without cationic liposomes is effective and could induce high and protective level of IBD antibody against IBDV challenged.